Internation tourism development in Vietnam and Malaysia - Trường Đại học Thủ Dầu Một (Đại học Quốc gia TP. Hồ Chí Minh, 2018)
Gồm có 3 phần: Phần 1. General overview on tourism. Phần 2. Tourism Space. Phần 3. Culture and communities in tourism